On the emergence and diffusion of technological capabilities and the theory of the MNC - Blomkvist, Katarina; Kappen, Philip; Zander, Ivo (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2015)
This paper intersects extant theories of the MNC with empirically observed patterns in the intra-company emergence and diffusion of technological capabilities. It draws upon a database containing the complete patenting history of 24 Swedish multinationals over the 1890-2008 period, which allows for the identification of when and where in the multinational organization new technological capabilities first emerged, and when and to where they subsequently diffused into other units of the multinational organization. The results reveal an increasing share of foreign-introduced technological capabilities, as well as distinctive and differentiated diffusion patterns across headquarters, greenfield subsidiaries, and acquired units in the MNC group. We conclude that a theory of the MNC should recognize the shift towards more equal conditions for the generation of new technology within the multinational organization, but that within this overall development some conspicuous inequalities in intra-company capability diffusion remain to be accounted for.